PENGARUH TINGKAT PENDIDIKAN DAN MASA KERJA TERHADAP KINERJA PEGAWAI REKTORAT UNIVERSITAS MULAWARMAN SAMARINDA - Damingun Damingun (Universitas Muhammadiyah Kalimantan Timur, 2018)
Based on F test results obtained Fcount> Ftable (235.661> 3.15) with Sig. F Change (0,000 <0,05) it can be concluded that H0 is rejected and Ha accepted which mean that education level (X1) and work period (X2) together give a significant influence to performance (Y) Civil Service Rectorate Mulawarman University Samarinda. From t test results obtained (X1) tcount> ttable (5,328> 1,6698) indicates that the variable of education level gives a significant influence, while (X2) tcount <ttable (0,092 <1,6698) indicating that variable of work period (X2 ) did not have a significant effect. This shows that the level of education is the dominant variable on the Performance of Civil Service Rectorate of Mulawarman University of Samarinda, this means acceptable hypothesis.